PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN AEROBIK ATLET SEKOLAH SEPAKBOLA PORSETA FC KECAMATAN LAREH SAGO HALABAN - Afdal Zikri; Apri Agus (JURNAL STAMINA, 2018)
The research problem is still not good Aerobic endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict, 50 Kota District. This study aims to determine the effect of interval training on aerobic endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict 50 Kota District. This type of research is experimental research. the population in this study were all of the Porseta Football School players Lareh Sago Halaban SubDistrict 50 Kota District., totaling 20 people. The sampling technique was by purposive sampling technique, the sample was taken from under 19 year players, amounting to 15 people. Data collection was carried out by pre-test and post-test. Aerobic Endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict 50 Kota District, using the Yo-Yo Intermitten Endurance Test. Data analysis and hypothesis testing using comparative analysis techniques using the mean difference test formula (t test) with a significant level of α = 0.05. From the data analysis, the results were obtained: The effect of interval training on aerobic endurance of Porseta Football School Athlete, Lareh Sago Halaban SubDistrict 50 Kota District, with the acquisition of "t" test coefficient, namely tcount = 8.81> t table = 1.76. Abstrak Masalah penelitian ini masih belum baik daya tahan aerobik Atlet Sekolah Sepakbola Porseta, Kecamatan Lareh Sago Halaban, 50 Kabupaten Kota. Penelitian ini bertujuan untuk mengetahui pengaruh latihan interval pada daya tahan aerobik Atlet Sekolah Sepakbola Porseta, Kecamatan Lareh Sago Halaban, Kecamatan 50 Kota. Jenis penelitian ini adalah penelitian eksperimental. Populasi dalam penelitian ini adalah semua pemain Sekolah Sepak Bola Porseta Lareh Sago Halaban Kecamatan 50 Kota., yang berjumlah 20 orang. Teknik pengambilan sampel menggunakan teknik purposive sampling, sampel diambil dari pemain berusia di bawah 19 tahun, berjumlah 15 orang. Pengumpulan data dilakukan dengan pre-test dan post-test. Ketahanan Aerobik Atlet Sekolah Sepak Bola Porseta, Kecamatan Lareh Sago Halaban, Distrik 50 Kota, menggunakan Uji Daya Tahan Yo-Yo Intermitten. Analisis data dan pengujian hipotesis menggunakan teknik analisis komparatif menggunakan rumus uji beda rata-rata (uji t) dengan taraf signifikan α = 0,05. Dari analisis data, diperoleh hasil: Pengaruh pelatihan interval pada daya tahan aerobik Atlet Sekolah Sepak Bola Porseta, Lareh Sago Halaban Kecamatan 50 Kota, dengan perolehan "t" koefisien uji, yaitu tcount = 8,81> t tabel = 1.76.